Women with Severe Anemia in Labor: Adverse Clinical Outcomes - Singh, Dr. Ruchika; Gupta, Dr. Mamta; Saini, Dr. Vandana (International Journal of Innovative Research in Medical Science, 2019)
Background: Severely anemic women in labor is a challenging situation for the obstetrician with increased perinatal and maternal morbidity and mortality. Methods: Evaluation of feto-maternal outcomes in women reporting in labor with severe anemia (group A, n=50) and without anemia (group B,n=50) was done. Results: No maternal mortality and still birth was observed in any of the group. Preterm labor pains, hypertensive disease, occurred more in group A (p value 0.003, 0.037 respectively). Blood transfusion was the commonest intervention required. Congestive heart failure developed (CHF) in 3 women in group A and none in group B. Mean birth weight was more in group B (p value 0.002). Birth asphyxia and NICU admissions were more in group A neonates (p value 0.012, 0.017 respectively). Puerperal morbidity was high in group A women (p value 0.001). Eight women had severe maternal morbidity and 1 woman had near miss event in severe anemia group. Conclusions: Severely anemic women reporting in labor have high maternal and perinatal morbidity.